Product Innovation as territory sustainable added value - the case study of Douro Skincare - Paiva, Teresa (2018)
Within a smart specialization context, regions and businesses have to develop their innovation and product delivery with added value to supply market needs in a different perspective. As the territory sustainability within the Portuguese smart specialization strategy (RIS3) is defined, we propose to exemplify through a case study a good practice in answering these new challenges. The case study explores the growth and regional involvement of Douro Skincare, a company created by women that operates in the field of selective biological cosmetics through the creation, development, and production of cosmetic lines that are based on emblematic raw materials of the Douro region, one of the oldest wine-growing areas, located in the north of our country, Portugal. It uses Douro grapes and PORT WINE DNA ™ (Douro Nuclear Aroma), created from the first Port wine from entirely organic production, to develop cosmetic lines produced with endogenous products. These types of territorial intensive products (TIPs) are associated directly with the region and are intensively endogenous, an answer to the challenges created within RIS3.